Pengaruh Leverage, Ukuran Perusahaan, Pertumbuhan Penjualan, Kepemilikan Manajerial dan Kepemilikan Institusional terhadap Financial Distress - Yola Zulkhaisi Utami; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to analyze the effect of leverage, firm size, sales growth, managerial ownership and institutional ownership on financial distress. This study uses annual report data for the consumer goods industry sector which is listed on the Indonesia Stock Exchange for 2016-2020. By using the purposive sampling method, 140 samples were obtained from 28 companies that made observations from 2016 - 2020. This study uses the zmijewski method as a measuring tool in predicting financial distress. This study uses multiple linear regression analysis in hypothesis testing. The results showed that leverage had a negative effect, company size and sales growth had no effect, and institutional ownership and ownership had a positive effect on financial distress.